Analysis of Innovation Technology Implementation and Risk-Based Internal Audits on Company Performance Optimization (Case Study of a Listed State- BUMN Bank) - Anisha Natasya; Ricky Agusiady; Haddan Dongoran (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The development of the Industrial Revolution 4.0 towards Society 5.0 is driving digital transformation in the banking sector, including state-owned banks listed on the Indonesia Stock Exchange. Global challenges, competition with private banks and fintech, and fraud risks require companies to optimize performance through the implementation of innovative technologies overseen by risk-based internal audits. This study aims to analyze and explain the application of innovative technologies and risk-based internal audits to company performance, analyze how risk-based internal audits encourage innovation and strengthen control mechanisms, and explain how the integration of both contributes simultaneously to performance optimization, particularly in the listed state-owned banking sector (Bank Mandiri, BNI, and BRI). This study uses a descriptive quantitative approach and verification through a literature review and secondary data for the 2023–2024 period. The results show that the implementation of innovative technologies such as Artificial Intelligence (AI), Big Data Analytics, Blockchain, and Robotic Process Automation (RPA) has a significant impact on improving company performance. This is evident in the increase in revenue, profit, ROA, and ROE at the three state-owned banks. The implementation of risk-based internal audits has been proven to drive innovation and efficiency through a digital audit system that accelerates the audit process, increases data accuracy, strengthens risk management, and improves fraud detection with the support of AI and data analytics. The results of the correlation test show a strong relationship between innovation technology and risk-based audits (r = 0.56), as well as between risk-based audits and company performance (r = 0.47), indicating that risk-based audits are an enabler for the effectiveness of innovation. The conclusion of the study is that innovation technology and risk-based internal audits result in more optimal, efficient, transparent, and sustainable company performance.